Cytogenetic studies in Phaseolus L. (Fabaceae) - Pedro Mercado-Ruaro; Alfonso Delgado-Salinas (Genetics and Molecular Biology, 2000)
A review of the cytogenetic studies carried out on Phaseolus as well as the different proposals that have been suggested to explain the chromosomal changes in the group are presented. The importance of including wild species in cytogenetic studies and the collaboration between taxonomists and cytogeneticists in order to draw better conclusions are emphasized.